Apoptosis-induced translocation of centromere protein F in its corresponding autoantibody production in hepatocellular carcinoma. (1st January 2021) - Li, Xiaojin; Li, Yanmeng; Xu, Anjian; Zhou, Donghu; Zhang, Bei; Qi, Saiping; Chen, Zhibin; Wang, Xiaoming; Ou, Xiaojuan; Cao, Bangwei; Qu, Chunfeng; Huang, Jian
ABSTRACT: Serum autoantibodies against tumor-associated antigen have important value in the early diagnosis of hepatocellular carcinoma (HCC), but the mechanism of autoantibody production is poorly understood. We previously showed that autoantibodies against the centromere protein F (CENPF) may be useful as an early diagnostic marker for HCC. Here we explored the mechanism of cell apoptosis-based CENPF autoantibody production and verified the correlation of CENPF autoantibody level with HCC development. We demonstrated that CENPF was overexpressed and aberrantly localized throughout the nuclei and cytoplasm in human HCC cells compared with hepatic cells. CENPF overexpression promoted the production of CENPF autoantibodies in a manner that correlated with tumor growth of mouse HCC model. During apoptosis of HCC cells, CENPF protein translocated to apoptotic vesicles and relocalized at the cell surface. Through isolating apoptotic components, we found apoptotic body and blebs with lower CD31 and CD47 expression more effectively induced DC phagocytosis and maturation compared with apoptotic intact cells in vitro, and this DC response was independent of CENPF expression. Moreover, injection of mice with apoptotic bodies and blebs effectively induced an immune response and the production of CENPF-specific antibodies. Our findings provide a first elucidation of mechanisms underlying the CENPF autoantibody production via cell apoptosis-induced CENPF translocation, and demonstrate a direct correlation between CENPF autoantibody levels and HCC progression, suggesting the potential of CENPF autoantibody as an HCC diagnostic marker.